2004
DOI: 10.1098/rspb.2004.2808
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and the adaptive utility of discrimination among alarm callers

Abstract: Unlike individually distinctive contact calls, or calls that aid in the recognition of young by their parents, the function or functions of individually distinctive alarm calls is less obvious. We conducted three experiments to study the importance of caller reliability in explaining individual-discriminative abilities in the alarm calls of yellow-bellied marmots (Marmota flaviventris). In our first two experiments, we found that calls from less reliable individuals and calls from individuals calling from a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
100
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(106 citation statements)
references
References 31 publications
(56 reference statements)
6
100
0
Order By: Relevance
“…Previous work has demonstrated that marmots are capable of discriminating among individuals based on their calls alone [11], and that assessing perceived caller reliability is likely to be the key factor that has selected for the evolution of discrimination abilities [47]. However, if discriminating among kin is an important function of individually distinctive calls, we would expect these individually distinctive factors to be heritable [38,39].…”
Section: Introductionmentioning
confidence: 82%
“…Previous work has demonstrated that marmots are capable of discriminating among individuals based on their calls alone [11], and that assessing perceived caller reliability is likely to be the key factor that has selected for the evolution of discrimination abilities [47]. However, if discriminating among kin is an important function of individually distinctive calls, we would expect these individually distinctive factors to be heritable [38,39].…”
Section: Introductionmentioning
confidence: 82%
“…Consequently, as has been predicted theoretically (28), false alarms may be an inevitable corollary of adaptive collective response in a dangerous and uncertain world. Previous observations of animal groups have found false alarms to be common, often accounting for a large proportion of overall alarms (50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…A third explanation is that including mimicry simulates a chorus of alarm calling species, thereby increasing the perceived urgency or reliability of alarm information. Not only may alarm calls from multiple callers be a more reliable indication of danger than alarm calls from a lone caller [25,26], but more dangerous predators, such as hawks, generally provoke aerial alarms from multiple species [27]. Regardless of the exact mechanism, we show that mimicry confers an anti-predator advantage.…”
Section: Discussionmentioning
confidence: 76%
“…As no flying predator is present, the production of aerial alarm calls by thornbills during nest defence conveys inaccurate information about danger and may serve to deceive predators into responding as if they themselves are in immediate danger from above [14,24]. Mimicking a chorus of aerial alarm calls may also simulate multiple callers, a reliable indication of immediate danger [20,[25][26][27], which may increase the effectiveness of deception.…”
Section: Introductionmentioning
confidence: 99%